Disintegrating Involvement in Second Life - Smith, David Harris (InTensions, 2009)
The following paper is a theoretical perspective on identity and embodiment disintegration in designed virtual sex involvements. The study data, derived from avatar sex participant interviews and virtual world field observations demonstrates the variance of enacted cognitive processes in the progressions of anticipatory desire and realized interactions. It is suggested that we design our selves and our worlds in anticipation of involvements and, reciprocally, in the acts of involving with these designed worlds and selves we, in turn, are progressively defined and modified. To designate worlds of potential involvement is to engage in a relentless struggle with incongruity. The empirical disintegration of self and world is an ongoing fact, emergent with ongoing re-designation and re-integration of self and world. This essay highlights the role of emphatic congruence assessments in the disintegrating involvements of avatar sex and intimacy.